Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 12 Sequences and Series - Chapter Review - Page 841: 11



Work Step by Step

The nth term of an arithmetic sequence can be obtained by the following formula: $a_n=a_1+(n-1)d$, where $a_1$ is the first term and $d$ is the common difference. Hence here: $a_11-a_4=7d\\42=7d\\d=6$ Then $a_4=(4-1)d+a_1\\27=3\cdot6+a_1\\a_1=9$ Thus $d=6,a_1=9,a_n=9+(n-1)6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.